(untitled) (Nativa, 2014)
Sete modelos empíricos (M1 a M7) baseados na temperatura do ar, foram ajustados e avaliados para estimar a irradiação solar global média horária mensal (Hgh) em quatro localidades do Estado de Alagoas, Brasil. Os dados foram medidos em estações solarimetricas automáticas situadas em Arapiraca (9°47’54,8”S e 37°36’23,4”W), Palmeira dos Índios (9°24’19,9”S e 36°39’22,7”W), Maceió (10°01’29,1”S e 36°16’29,1”W) e Coruripe (9°28’29,1”S e 35°49’43,6”W), entre 2007 e 2009. Para indicar o desempenho dos modelos utilizaram-se os indicativos estatísticos: desvio das médias (MBE), raiz quadrada do desvio quadrático médio (RMSE), “d” de Willmott e teste-t. Os coeficientes ajustados (β1 e β2) dos modelos foram dependentes da região e dos efeitos climáticos locais. Os coeficientes β2 dos M1, M2 e M3 foram significativos a 5%, enquanto que, o coeficiente β1 de M4 e M5 resultaram em comportamentos semelhantes. Os coeficientes β1 e β2 de M6 e M7 apresentaram elevadas oscilações. Com RMSE médio de 0,29 ± 0,15 MJ m-2h-1, o melhor ajuste para região de Arapiraca foi com M7. O melhor ajuste para as condições climáticas nas regiões de Palmeira dos Índios, Maceió e Coruripe foi com M4. Estes resultados mostram a eficiência dos modelos empíricos em prever Hgh. Palavras-chave: Modelos empíricos, Bristow e Campbell, Hargreaves e Samani, condições climáticas. MODELLING OF MONTHLY HOURLY GLOBAL SOLAR IRRADIATION (Hgh) TO FOUR SITES IN ALAGOAS/BRAZIL ABSTRACT In this paper was used seven empirical models (M1 to M7) based on temperature of air and they were fitted and validated to estimating the monthly hourly of global solar irradiation (Hgh) in four sites in Alagoas State, Brazil. The data were measured in automatic solarimetric stations situated in Arapiraca (9°47’54.8”S and 37°36’23.4”W), Palmeira dos Índios (9°24’19.9”S and 36°39’22.7”W), Maceió (10°01’29.1”S and 36°16’29.1”W) and Coruripe (9°28’29.1”S and 35°49’43.6”W), from 2007 to 2009. To indicate the models performance were used: Mean Bias Error (MBE), Root Mean Square Error (RMSE), “d” of Willmott and t-test. The fitted coefficients (β1 and β2) of models were dependents of region and local climatic effects. The coefficients β2 of M1, M2 and M3 were significantly different at the level of 5%. The β1 coefficient of M4 and M5 resulted in similar oscillations. The β1 and β2 coefficients of M6 and M7 presented high oscillations. With RMSE average of 0.29±0.15 MJ m-2 h-1, the best fitted model for the Arapiraca region was M7. The best fitted model for the climatic conditions in the region of Palmeira dos Índios, Maceió and Coruripe were M4. The M4 generated the best result among the evaluated models. These results showed the efficiency of the empirical models to predict Hgh. Keywords: Empirical models, Bristow and Campbell, Hargreaves and Samani, Climatic conditions. DOI: http://dx.doi.org/10.14583/2318-7670.v02n02a04